Answers

2015-11-08T18:08:15+05:30
COTA-COT2A=COSEC2A
COSA/SINA -COS2A/SIN2A=1/SIN2A
SIN2ACOSA/COSA -COS2ASINA/SINA=1
SIN2ACOSA-COS2ASINA=SINA
SIN(2A-A)=SINA
SINA=SINA

Hope my answer helps u....





0
2015-11-08T18:12:02+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Prove that,
cotA-cot2A = cosec2A
LHS = cotA-cot2A
        = cosA/sinA - cos2A/sin2A
        = (cosA.sin2A - cos2A.sinA)/sinA.sin2A
        = (sin2A.cosA-cos2A.sinA)/sinA.sin2A
        = sin(2A-A)/sinA.sin2A
        = sinA/sinA.sin2A
        = 1/sin2A
        = cosec2A 
L.H.S = R.H.S
1 5 1